Spheroid size influences cellular senescence and angiogenic potential of mesenchymal stromal cell-derived soluble factors and extracellular vesicles - Rovere, Matteo; Reverberi, Daniele; Arnaldi, Pietro; Palamà, Maria Elisabetta Federica; Gentili, Chiara (Frontiers in Bioengineering and Biotechnology, 2023)
The secretome of mesenchymal stromal cells (MSCs) serves as an innovative tool employed in the regenerative medicine approach. In this particular context, three-dimensional (3D) culture systems are widely utilized to better replicate in vivo conditions and facilitate prolonged cell maintenance during culture. The use of spheroids enables the preservation of the classical phenotypical characteristics of MSCs. However, the distinct microenvironment within the spheroid may impact the secretome, thereby enhancing the angiogenic properties of adult MSCs, that typically possess a reduced angiogenic potential compared to MSCs derived from peri-natal tissues, due to the hypoxia created in the internal region of the spheroid. In this study Large spheroids (2,600 cells, ~ 300 μm diameter) and Small spheroids (1,000 cells, ~ 200 μm diameter) were used to examine the role of spheroid diameter on the generation of nutrients and oxygen gradients, cellular senescence, and angiogenic potential of secreted factors and extracellular vesicles (EVs). In this study we demonstrate that Large spheroids showed increased senescence and a secretome enriched in pro-angiogenic factors but also in pro-inflammatory and anti-angiogenic cytokines, while Small spheroids exhibited decreased senescence and a secretome enriched in pro-angiogenic molecules. We also demonstrated that 3D culture led to a higher secretion of EVs with classical phenotypic characteristics. Soluble factors and EVs from Small spheroids exhibited higher angiogenic potential in a HUVECs angiogenic assay. These findings highlighted the necessity to choose the appropriate culture system for obtaining soluble factors and EVs for specific therapeutic applications.